2008
DOI: 10.1016/j.expneurol.2008.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Dopaminergic dysfunction in DYT1 dystonia

Abstract: A three-base-pair deletion in the torsinA gene leads to generalized torsion dystonia (DYT1) in humans, an often devastating movement disorder in which voluntary movements are disrupted by sustained muscle spasms and abnormal limb posturing. In a recent issue of Experimental Neurology, Zhao et al. (2008) have provided a thorough behavioral, anatomic, and biochemical characterization of a mouse line that over-expresses human mutant torsinA, with particular emphasis on the possible role of dopaminergic dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 83 publications
(116 reference statements)
3
43
0
Order By: Relevance
“…Some forms of dystonia are clearly associated with basal ganglia dysfunction. For instance, dystonia may result from disturbances in dopaminergic transmission assumed to affect strongly basal ganglia activity [183]. Thus, dystonia may develop either acutely or delayed (tardive dystonia), in normal individuals treated with dopamine-receptor blocking agents, or can be a sign of other diseases with disturbed dopamine metabolism, such as PD, levodopa-responsive dystonia, or DYT1 [184][185][186][187][188][189].…”
Section: Dystoniamentioning
confidence: 99%
“…Some forms of dystonia are clearly associated with basal ganglia dysfunction. For instance, dystonia may result from disturbances in dopaminergic transmission assumed to affect strongly basal ganglia activity [183]. Thus, dystonia may develop either acutely or delayed (tardive dystonia), in normal individuals treated with dopamine-receptor blocking agents, or can be a sign of other diseases with disturbed dopamine metabolism, such as PD, levodopa-responsive dystonia, or DYT1 [184][185][186][187][188][189].…”
Section: Dystoniamentioning
confidence: 99%
“…We speculate that in mut-Tg mice, neurons are more vulnerable to elevated calcium levels and thus develop hyperexcitability when challenged with coffee, alcohol, or stress. In our mutant PNKD mouse model and other generalized dystonia mouse models, dysregulated dopamine signaling has been demonstrated in the striatum (10,(33)(34)(35)(36)(37).…”
mentioning
confidence: 90%
“…Multiple lines of evidence suggest a role for abnormalities of the DA system in the pathophysiology of dystonia (reviewed in Wichmann, 2008). Previous studies in torsinA transgenic and knockdown mice have shown alterations in striatal levels of DA and/or its metabolites (Dang et al 2005, 2006; Grundmann et al, 2007; Zhao et al 2008); however, as both increases and decreases have been reported, the question of how the DA system is affected remains unresolved.…”
Section: Introductionmentioning
confidence: 99%